1966
DOI: 10.1017/s0022143000019080
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Origin of Superglacial Drift on the Glaciers of the Martin River Area, South-Central Alaska

Abstract: D epartmen t of Geology and Geography, M usking um College, N ew Concord , Ohio, U S A.) MARTI N RIVER GLACIER a nd a sm a ll glacier for w hich the informa l n a m e " Sioux G lacier" will be used here (Fig . I ; !at. 600 24' to 60 0 35' N ., long. 143 0 30' to 1440 25' W .) are m antled with la rge q uantities of rock d ebris. A series of p hotographs da ti ng fro m 1938 to 1964 a nd the geom orphic m odifica tions resulting from the A laska n earthq ua ke (27 M arch 1964) suggest rock avalanching as a n or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1967
1967
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Photographs of this glacier taken before the 1964 earthquake display a rock-slide avalanche deposit covering more than 1 km. 2 which was identified by Tuthill (1966). Except for this, the glacier prior to 1964 was relatively clear of debris, indicating that this rock avalanche was an isolated occurrence.…”
Section: Sioux Glacier Debrismentioning
confidence: 84%
See 1 more Smart Citation
“…Photographs of this glacier taken before the 1964 earthquake display a rock-slide avalanche deposit covering more than 1 km. 2 which was identified by Tuthill (1966). Except for this, the glacier prior to 1964 was relatively clear of debris, indicating that this rock avalanche was an isolated occurrence.…”
Section: Sioux Glacier Debrismentioning
confidence: 84%
“…Tuthill (1966) has suggested that former earthquake-avalanching was the primary source of the debris on the lower part of Martin River Glacier. This appears unlikely for the following reasons: Source areas for large-scale rock-slide avalanches are absent in the lower valley where the debris is located. If avalanching occurred in the lower valley, lateral moraines and medial moraines on the glacier would have been covered.…”
mentioning
confidence: 99%
“…No specific attempt was made to determine the average thickness of the cover, but numerous random observations indicate that it is probably about 2 m. The total volume of rock debris deposited by this slide is approximately 6000000 m 3 . Tuthill (1966, p. 86) estimated the total volume of the snow and rock debris was 8300000 m 3 , but recalculation of data presented by Tuthill and Laird (1966, p. B17) suggests the volume was 9300000 m 3 , of which 2300000 m 3 was rock debris (personal communication from S. J. Tuthill).…”
Section: Characteristics Of the Debris Slidementioning
confidence: 99%
“…Numerous publications have resulted from the first 3 years of glacial research, including those by Reid and Clayton (1963), Tuthill (1963, 1966), Clayton (1964), Laird and Tuthill (1964), Reid and Callender (1965), Tuthill and Laird (1966), and Reid (1967). Other authors have reported the existence of the debris slide on “Sioux Glacier” subsequent to the Good Friday earthquake (Grantz and others, 1964; Post, 1965, 1967; Ragle and others, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Stagnation of glacial ice has been observed in modern glaciers, such as Martin River Glacier (Clayton, 1964;Tuthill, 1966), Muir Glacier (Haselton, 1966), Adams Glacier in Glacier Bay (McKenzie, 1970), and Burroughs Glacier (Mickelson, 1971), all located in Alaska, and in many other glaciers around the world. In many cases the stagnant ice became covered with ablation till and melted more slowly compared to the clean ice up-glacier.…”
Section: Introductionmentioning
confidence: 99%